Aminophylline Induces Two Types of Arrhythmic Events in Human Pluripotent Stem Cell–Derived Cardiomyocytes - Klimovic, Simon; Scurek, Martin; Pesl, Martin; Beckerova, Deborah; Jelinkova, Sarka; Urban, Tomas; Kabanov, Daniil; Starek, Zdenek; Bebarova, Marketa; Pribyl, Jan; Rotrekl, Vladimir; Brat, Kristian (Frontiers in Pharmacology, 2022)
Cardiac side effects of some pulmonary drugs are observed in clinical practice. Aminophylline, a methylxanthine bronchodilator with documented proarrhythmic action, may serve as an example. Data on the action of aminophylline on cardiac cell electrophysiology and contractility are not available. Hence, this study was focused on the analysis of changes in the beat rate and contraction force of human pluripotent stem cell–derived cardiomyocytes (hPSC-CMs) and HL-1 cardiomyocytes in the presence of increasing concentrations of aminophylline (10 µM–10 mM in hPSC-CM and 8–512 µM in HL-1 cardiomyocytes). Basic biomedical parameters, namely, the beat rate (BR) and contraction force, were assessed in hPSC-CMs using an atomic force microscope (AFM). The beat rate changes under aminophylline were also examined on the HL-1 cardiac muscle cell line via a multielectrode array (MEA). Additionally, calcium imaging was used to evaluate the effect of aminophylline on intracellular Ca2+ dynamics in HL-1 cardiomyocytes. The BR was significantly increased after the application of aminophylline both in hPSC-CMs (with 10 mM aminophylline) and in HL-1 cardiomyocytes (with 256 and 512 µM aminophylline) in comparison with controls. A significant increase in the contraction force was also observed in hPSC-CMs with 10 µM aminophylline (a similar trend was visible at higher concentrations as well). We demonstrated that all aminophylline concentrations significantly increased the frequency of rhythm irregularities (extreme interbeat intervals) both in hPSC-CMs and HL-1 cells. The occurrence of the calcium sparks in HL-1 cardiomyocytes was significantly increased with the presence of 512 µM aminophylline. We conclude that the observed aberrant cardiomyocyte response to aminophylline suggests an arrhythmogenic potential of the drug. The acquired data represent a missing link between the arrhythmic events related to the aminophylline/theophylline treatment in clinical practice and describe cellular mechanisms of methylxanthine arrhythmogenesis. An AFM combined with hPSC-CMs may serve as a robust platform for direct drug effect screening.